Assessment of Dental Caries among adults of different Socioeconomic groups - Mahpara Safdar, Hafiz Muhammad Tufail, Kiran Fatima, Amna Mahmood, Hamadia, Saadia Ch, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental caries is one of the leading dental diseases worldwide. Its towering prevalence in all age groups is worrisome and it lies in the top ten most common chronic health conditions. Interplay of biological, environmental, social, and behavioral elements forms its etiology. Recently, there has been growing research which has looked at the environmental and social factors that impact the oral health of people in different age groups. Aim: To determine the frequency of dental carries among participants belonging to different socioeconomic groups. Methods: It was adescriptive cross-sectional study. The study was carried out at Dental department of Begum Haseena Memorial Medical Center, Wah Cantt from 15th February 2019 till 15 August 2019. Three hundred participants (36 men and 264 women) aged 19-60 years were included through non-probability consecutive sampling. Results: Total of 300 patients belonging to different socio-economic groups were included in study. Most of the respondents were from lower SES which comprised of 74% of the total sample size. Highest number of respondents fell in the age range of 28-35 i.e., 37%. SES was assigned by calculating per capita income through total income from all sources divided by number of households dependent on that income. Interviews were conducted and statistical analysis was done using correlation and multiple linear regression which revealed significant association between SES and DC (p <0.05).The prognosis of dental health diseases can be predicted by using socioeconomic status as an indicator. Conclusion: Prevalence of dental health diseases can be decreased through cost effective prevention strategies which should pivot around spreading awareness among masses about the undesirable outcomes of oral health diseases and educating them about the importance of good oral hygiene.